Feasibility and Impact of a Combined Supervised Exercise and Nutritional-Behavioral Intervention following Bariatric Surgery: A Pilot Study - Friedrich C. Jassil; Sean Manning; Neville Lewis; Siri Steinmo; Helen Kingett; Fiona Lough; Andrea B. F. Pucci; W. H. Cheung; Nicholas Finer; Judith Walker; Jaqueline Doyle; Rachel L. Batterham (Journal of Obesity)
Background. Lifestyle intervention programs after bariatric surgery have been suggested to maximise health outcomes. This pilot study aimed to investigate the feasibility and impact of an 8-week combined supervised exercise with nutritional-behavioral intervention following Roux-en-Y gastric bypass and sleeve gastrectomy. Methods. Eight female patients (44 ± 8 years old, BMI = 38.5 ± 7.2 kgm−2) completed the program. Before and after intervention, anthropometric measures, six-minute walk test (6MWT), physical activity level, eating behavior, and quality of life (QoL) were assessed. Percentage weight loss (%WL) outcomes were compared with a historical matched control group. Results. The program significantly improved functional capacity (mean increment in 6MWT was 127 ± 107 meters, p=0.043), increased strenuous intensity exercise (44 ± 49 min/week, p=0.043), increased consumption of fruits and vegetables (p=0.034), reduced consumption of ready meals (p=0.034), and improved “Change in Health” in QoL domain (p=0.039). The intervention group exhibited greater %WL in the 3–12-month postsurgery period compared to historical controls, 12.2 ± 7.5% versus 5.1 ± 5.4%, respectively (p=0.027). Conclusions. Lifestyle intervention program following bariatric surgery is feasible and resulted in several beneficial outcomes. A large randomised control trial is now warranted.